The Management Analysis of Habituation Program of Weekly Morning Arabic Conversation at SMP Maarif 12 Pamekasan - Syamsul Hadi; Moh. Tohiri Habib (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The purpose of this study is to analyse the management of habituation program of weekly morning Arabic conversation at SMP Maarif 12 Pamekasan from the aspect of planning, actuating and evaluating. The study used qualitative approach with a descriptive-analytical method by choosing the subject purposively namely the principle, Arabic teacher and student. The data collection technique used observation non participative, deep interview and document analysis. The data analysis used the analysis model of Miles and Huberman. Beginning with data reduction, data display and conclusion drawing. The study result show that the effectivity of habituation program of Arabic conversation is not only determined by the intensity of speaking practice but also the consistent and structured management program. In the planning aspect, the program is designed based on the students’ need analysis as well as clear objectives and mechanism. In the actuating aspects, the routine paired conversations practice reinforced by the teacher guidance reflect the strategy of efficient implementation design within the time limitation of formal school. In the evaluation aspect, the formative evaluation conducted through observing the development of students’ fluency and self-confidence as well as implementer’s internal reflection. Analytically, the integration of planning, actuating and evaluating is the key factor of effectiveness and sustainability of Arabic habituation program in the formal school. This study contributes to the development of the management study of Arabic program by positioning the habituation of Arabic conversation as both a pedagogical and managerial practice which require systematic design and sustainable evaluation.